Novel missense and 3′-UTR splice site variants in LHFPL5 cause autosomal recessive nonsyndromic hearing impairment. Issue 11 (November 2018) - Liaqat, Khurram; Chiu, Ilene; Lee, Kwanghyuk; Chakchouk, Imen; Andrade-Elizondo, Paula; Santos-Cortez, Regie; Hussain, Shabir; Nawaz, Shoaib; Ansar, Muhammad; Khan, Muhammad; Basit, Sulman; Schrauwen, Isabelle; et al.
Abstract LHFPL5, the gene for DFNB67, underlies autosomal recessive nonsyndromic hearing impairment. We identified seven Pakistani families that mapped to 6p21.31, which includes theLHFPL5 gene. Sanger sequencing ofLHFPL5 using DNA samples from hearing impaired and unaffected members of these seven families identified four variants. Among the identified variants, two were novel: one missense c.452 G > T (p.Gly151Val) and one splice site variant (c.*16 + 1 G > A) were each identified in two families. Two known variants: c.250delC (p.Leu84*) and c.380 A > G (p.Tyr127Cys) were also observed in two families and a single family, respectively. Nucleotides c.452G and c.*16 + 1G and amino-acid residue p.Gly151 are under strong evolutionary conservation. In silico bioinformatics analyses predicted these variants to be damaging. The splice site variant (c.*16 + 1 G > A) is predicted to affect pre-mRNA splicing and a loss of the 5′ donor splice site in the 3′-untranslated region (3′-UTR). Further analysis supports the activation of a cryptic splice site approximately 357-bp downstream, leading to an extended 3′-UTR with additional regulatory motifs. In conclusion, we identified two novel variants inLHFPL5, including a unique 3′-UTR splice site variant that is predicted to impact pre-mRNA splicing and regulation through an extended 3′-UTR.